Bringing Which State Back In? - Naylor, James (Labour / Le Travail, 1995)
The article reviews several books including "Labor Visions and State Power: The Origins of Business Unionism in the United States," by Victoria C. Hattam, "The Experience of Workers in the United States With Democracy and the Free Market During the Nineteenth Century," by David Montgomery and "The State and Labor in Modern America," by Melvyn Dubofsky.
Keywords: BOOKS – Reviews; DUBOFSKY; Melvyn; EXPERIENCE of Workers in the United States With Democracy & the Free Market During the 19th Century; The (Book); HATTAM; Victoria C.; LABOR Visions & State Power: The Origins of Business Unionism in the United States (Book); MONTGOMERY; David; Nonfiction; STATE & Labor in Modern America; The (Book)